Mate availability determines use of alternative reproductive phenotypes in hermaphrodites. (20th May 2020) - Felmy, Anja; Weissert, Nora; Travis, Joseph; Jokela, Jukka
Abstract: In many species, individuals can employ alternative reproductive phenotypes, with profound consequences for individual fitness and population dynamics. This is particularly relevant for self-compatible hermaphrodites, which have exceptionally many reproductive options. Here we investigated the occurrence of reproductive phenotypes in the simultaneously hermaphroditic freshwater snail Radix balthica under experimentally simulated conditions of low versus moderate population density. We captured all mating behavior on camera and measured individual female lifetime reproductive success. We found every possible reproductive phenotype: (1) both male and female (i.e., truly hermaphroditic) reproduction, (2) purely female and (3) purely male reproduction, (4) male reproduction combined with self-fertilization and (5) female mating activity, (6) pure self-fertilization without mating and (7–8) two types of reproductive failure. Variation in alternative reproductive phenotypes was explained by mate availability (10.8%) and individual condition, approximated by a snail's mean daily growth rate (17.5%). Increased mate availability resulted in a lower diversity of reproductive phenotypes, in particular increasing the frequency of true hermaphrodites. However, it lowered phenotype-specific fecundities and hence reduced the population growth rate. Snails in better condition were more likely to reproduce as true hermaphrodites or pure females, whereas low-condition snails tended to suffer reproductive failure. Overall, we show substantial variation in alternative reproductive phenotypes in a hermaphrodite, which is possibly in part maintained by fluctuations in population density and thus mate availability, and by variation in individual condition. We also provide evidence of an almost 2-fold increase in clutch size that can be ascribed specifically to mating as a female. Abstract : Hermaphroditic snails can show a stunning diversity of alternative reproductive phenotypes within a single population. Using laboratory experiments, we show that snails employ one of eight reproductive phenotypes, including pure self-fertilization, pure male, pure female, and truly hermaphroditic reproduction, depending on mate availability and their overall condition. Female lifetime reproductive success is not equal for all phenotypes, so changes in the distribution of phenotypes will have consequences for the dynamics of snail populations.